Pembuatan Motion Graphic Sebagai Media Informasi Bagi Pengunjung Di PT Pembangunan Jaya Ancol: The Production Of Motion Graphics As An Information Media For Visitors At PT Pembangunan Jaya Ancol - Sascorio Ade Akbar; Amata Fami; Novi Asri Maharani (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2019)
ABSTRACT This final assignment was created with the aim of making multimedia content in the form of motion graphics. The content is expected to be an alternative content for Taman Impian Jaya Ancol which is published to its visitors, especially for increasing their brand value. The Production of Motion Graphics as an Information Media for Visitors at PT Pembangunan Jaya Ancol were using my own development method. The results of this final assignment were in the form of six video products in the form of motion graphics and two of them as information media for Taman Impian Jaya Ancol’s visitors. ABSTRAK Tugas Akhir dibuat dengan tujuan membuat konten multimedia dengan bentuk motion graphic. Konten ini diharapkan menjadi konten alternatif bagi pihak Taman Impian Jaya Ancol yang akan dipublikasikan kepada pengunjung. Di sisi lain pembuatan konten juga dapat meningkatkan brand value Taman Impian Jaya Ancol PT kepada audience. Pembuatan motion graphic sebagai media informasi bagi pengunjung di PT Pembangunan Jaya Ancol ini menggunakan metode pengembangan sendiri. Hasil dari kegiatan PKL berupa enam produk video berbentuk motion graphic dan dua diantaranya sebagai media informasi bagi pengunjung Taman Impian Jaya Ancol.